Relationship between lichen diversity and air quality in urban region in Bourdj Bou Arriridj, Algeria - Messaoud Ramdani; Fatima Adjiri; Takia Lograda (Society for Indonesian Biodiversity, 2019)
Abstract. Fatima A, Messaoud R, Takia L. 2019. Relationship between lichen diversity and air quality in urban region in Bourdj Bou Arriridj, Algeria. Biodiversitas 20: 2329-2339. The lichenic biodiversity can be an excellent instrument for measuring air quality biomonitoring in urban and industrial areas. Two bio-monitoring techniques were used to assess and map the levels of air quality in Bordj Bou Arreridj region (BBA), an urban area located in Eastern Algeria, and to identify species sensitive to air pollution. The first one was based on the diversity and abundance of epiphytic lichens, while the other technique was using two bio-indication indices. Epiphytic lichens were sampled from thirty-four stations chosen on the basis of the presence of suitable phorophytes on which it is possible to observe lichens. The assessment of lichen biodiversity was based on the calculation of lichenic abundance indices (LA) and the Shannon index (H'). For the determination of the different levels of air pollution, the indices of atmospheric purity (IAP) and lichen diversity (LDV) were used. There were 62 identified species belong to 19 families and 31 genera of lichens, among which crustacean and foliose thalli were the most common in the region. Lichen biodiversity decreased as the sampled location approaching industrial sources and road traffic. The IAP ranged from 16.19-79.82 and LDV values ranged from 12.50-52.16. The results showed a significant relationship between lichen diversity and air quality, and indicated low atmospheric pollution in the BBA region. This study allowed us to draw up a list of sensitive species and tolerant species to air pollution.